Geospatial Celebration of Sidomulyo Village: A Spatial Analysis of Tourist Village Development - Nasobi Niki Suma; Achmad Tedy Hariyanto; Achmad Farichin Zuber; Esti Yulia W.; Khoirotusaniyah Khoirotusaniyah; Nila Rohmatul Ula; Syela Faizah (Institut Agama Islam Negeri Jember, 2022)
Sidomulyo Village is on the outskirts of a forest located at the eastern end of Jember Regency, East Java. The village's location, on the outskirts of the forest and surrounded by the Gumitir Mountains, is a challenge in developing this village. In addition, the extended access to the city center has made Sidomulyo Village receive less attention from the district government and investors. A touch of creative and innovative village programs to introduce this village to the broader community needs to be done. One of the program breakthroughs in Sidomulyo Village was a series of activities summarized in the ”Sidomulyo Village Celebration” event. The aims of this study were (1) to find out the objectives and program activities in the